2019
DOI: 10.7150/thno.27891
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Radiolabelling of Exosomes for Comparative Biodistribution Analysis in Immunocompetent and Immunodeficient Mice - A Novel and Universal Approach

Abstract: Extracellular vesicles, in particular exosomes, have recently gained interest as novel drug delivery vectors due to their biological origin and inherent intercellular biomolecule delivery capability. An in-depth knowledge of their in vivo biodistribution is therefore essential. This work aimed to develop a novel, reliable and universal method to radiolabel exosomes to study their in vivo biodistribution. Methods : Melanoma (B16F10) cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
109
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(122 citation statements)
references
References 78 publications
8
109
1
Order By: Relevance
“…The preferential uptake of PANC-1 Exo by their parent PANC-1 cells was recapitulated in vivo, as demonstrated by the significantly higher uptake of the former in PANC-1 tumours than that in the more vascularised B16-F10 tumours ( Figure 6) [42]. It is worth noting that although B16-F10 cells were predicted by the DoE modelling to show preferential uptake of self-B16-F10 Exo in vitro in this study, which was observed with actual experimental investigation in our previous work, preferential uptake by B16-F10 tumours was not observed in vivo in the same previous study [32]. It was described earlier that expression of CD47 on exosome membranes confers protection from clearance by circulating macrophages and therefore prolongs the circulation time of exosomes in vivo [5].…”
Section: Discussionsupporting
confidence: 87%
“…The preferential uptake of PANC-1 Exo by their parent PANC-1 cells was recapitulated in vivo, as demonstrated by the significantly higher uptake of the former in PANC-1 tumours than that in the more vascularised B16-F10 tumours ( Figure 6) [42]. It is worth noting that although B16-F10 cells were predicted by the DoE modelling to show preferential uptake of self-B16-F10 Exo in vitro in this study, which was observed with actual experimental investigation in our previous work, preferential uptake by B16-F10 tumours was not observed in vivo in the same previous study [32]. It was described earlier that expression of CD47 on exosome membranes confers protection from clearance by circulating macrophages and therefore prolongs the circulation time of exosomes in vivo [5].…”
Section: Discussionsupporting
confidence: 87%
“…100 An alternate approach for biodistribution analysis is membrane radiolabeling of exosomes. 101 It is worth emphasizing that although this review of the literature is focused on the delivery of therapeutic exosomes, endogenous EVs play detrimental roles in a number of pathological processes, including MI. 47 Distinct strategies are aimed at blocking the assembly, release and uptake of endogenous EVs, 102 modifying their composition, and removing them from the circulation.…”
Section: Current Limitations and Challengesmentioning
confidence: 99%
“…Ultracentrifugation (UC)-based isolation is the most commonly used technique [ 51 , 54 , 55 , 56 , 57 , 58 , 59 ] according to a worldwide International Society for Extracellular Vesicles (ISEV) survey [ 60 ].…”
Section: Centrifugation-based Isolation Techniquesmentioning
confidence: 99%